EFEKTIFITAS PEMBELAJARAN IPA MENGGUNAKAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI CARA MENGHASILKAN ENERGI LISTRIK PADA SISWA KELAS VI SDN 01 BILAH HILIR - Saidah Saidah (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
This research aims to (1) find out whether there is an increase in student learning outcomes by using the Problem Based Learning learning model in the material How to produce electrical energy in class VI students at SDN 01 Bilah Hilir (2) How to apply the Problem Based Learning model in improving student learning outcomes in material How to produce electrical energy. This research is Classroom Action Research. The subjects of this research were Class VI students at SDN 01 Bilah Hilir, Bilah Hilir District, Labuhanbatu Regency with a total of 24 students studied. The object of this research is to improve student learning outcomes in science learning using the Problem Based Learning Model. Based on the research results and discussion, it can be concluded that the results of science learning with material on how to produce electrical energy have increased using the Problem Based Learning Model for class VI students at SDN 01 Bilah Hilir, Bilah Hilir District, Academic Year 2022/2023. The average for the first cycle class increased from the initial test by 6.67% (62.08% to 68.75%), while the percentage of students' classical abilities increased by 12.50% (58.33% to 70.83%) . The class average in cycle II increased from cycle I by 13.33% (68.75% to 82.08%). Meanwhile, his classical ability increased by 16.67% (70.83% to 87.50%). Students' attitudes towards receiving learning using science learning with the problem based learning model were very positive because in cycle I student activity in participating in science learning with the problem based learning model was 67.86% and increased in cycle II to 85.71% where the increase in student observations increased. amounting to 17.85%. Meanwhile, teacher observations increased by 13.46%, where in the first cycle it was 73.08%, increasing in the second cycle to 86.54%.